2022
DOI: 10.1007/s40257-022-00674-3
|View full text |Cite|
|
Sign up to set email alerts
|

A Review of Existing Therapies for Actinic Keratosis: Current Status and Future Directions

Abstract: Actinic keratosis (AK) is a chronic skin disease in which clinical and subclinical cutaneous lesions coexist on sun-exposed areas such as the head and neck region and the extremities. The high prevalence of AK means the disease burden is substantial, especially in middle-aged and elderly populations. Evidence indicates that AK may progress into invasive cutaneous squamous cell carcinoma, so the European guidelines recommend treatment of any AK regardless of clinical severity. Given the aging population and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 92 publications
1
32
0
2
Order By: Relevance
“…Ideally, actinic keratosis treatment should remove as many clinical and subclinical lesions as possible, achieve a long-lasting clinical remission, produce a pleasing cosmetic outcome, and stop the development of invasive squamous cell carcinoma 53 . Current standards of care for AK patients rely on lesion-directed procedures or topical field therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, actinic keratosis treatment should remove as many clinical and subclinical lesions as possible, achieve a long-lasting clinical remission, produce a pleasing cosmetic outcome, and stop the development of invasive squamous cell carcinoma 53 . Current standards of care for AK patients rely on lesion-directed procedures or topical field therapies.…”
Section: Discussionmentioning
confidence: 99%
“…All three topical treatments are FDA-approved for AK and have reported response rates of 40%-80% for AKs, with 5-FU being most effective. 9 5-FU and IMQ are also FDA-approved to treat superficial BCC, and studies have shown therapeutic effects when applied to the treatment of superficial SCC. 10 Although each of these topical agents can treat multiple, diffuse lesions (thereby addressing the 'field cancerization' problem) and often result in an overall higher rate of long-term clearance than cryotherapy, each is also associated with an intense local skin reaction characterised by pain, burning, skin erosions and, in some instances, hyper-or hypopigmentation of the skin.…”
Section: Introductionmentioning
confidence: 99%
“…To address the high statistical risk of cancer arising within these regions, several non‐invasive topical treatments are currently approved, including fluorouracil (5‐FU; an antimetabolite), imiquimod (IMQ; an immunomodulator), and tirbanibulin (a microtubule inhibitor). All three topical treatments are FDA‐approved for AK and have reported response rates of 40%–80% for AKs, with 5‐FU being most effective 9 . 5‐FU and IMQ are also FDA‐approved to treat superficial BCC, and studies have shown therapeutic effects when applied to the treatment of superficial SCC 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Areas of the skin often affected include the face (especially the nose and forehead), the forearms and backs of hands, on the rims of the ears and bald scalps in men and on the legs below the knees in women 5 . Populations frequently impacted by AKs include the elderly who in addition to cumulative sun exposure also have higher rates of co‐morbidities and polymedication that may interfere with treatment 8,9 …”
Section: Introductionmentioning
confidence: 99%